KRISIS EKONOMI DAN KEGIATAN EKONOMI WANITA PEDESAAN - Hastuti, Hastuti (Jurnal Penelitian Humaniora, 2015)
Abstract The research in Donohardjo, Ngaglik, Sleman, has two objects: 1) to know the effect of the economic crisis on the women's economic activities in rural areas, 2) to know the differences between the incomes from the women's economic activities in the rural area before and after the economic crisis. The result of the research shows that the wide of the area or land is up to 660.9 ha. Most of the areas which have been used for the agricultural activities, are up to 63%. The ownership of the small field is indicated by the fact that 72.5% village respondents have the land or field less than 0.25 ha. The economic crisis which has begun since 1997 has influenced most of the farmers in the research areas in retaining the continuity of their agricultural activities, because of the delay in getting the facilities of the agricultural production, marketing the product and providing the facilities of the agricultural production, marketing the product and providing the capital, work place, competed ability and workforce are only done by62.5% of the women. Te economic crisis influences the quality of rural women's income Keywords: economic crisis, economic activities of women's rural